Components and Treatments of Oilfield Produced Water - Al-Haleem, Ayad A.; Abdulah, Hamed H.; Saeed, Essam Abdul-Jalil (Al-Khwarizmi Engineering Journal, 2010)
In this study, a review of variety of processes that are used in the treatment produced water prior to reuse or to responsible disposal are presented with their environmental issues and economical benefits. Samples of produced water from five locations in Rumaila oilfield/in south of Iraq were taken and analyzed for their contents of brine, some heavy metals, total suspended solids and oil and grease. Moreover, two samples of water were treated using reverse osmosis technique which showed its ability to treat such contaminated water. The results showed that the environmental impact of produced water arises from its chemical composition; i.e., its salt content, its heavy metals, and hydrocarbon contents.